Conservative management of severe intrusion in a primary tooth: A 4-year follow-up - Ruviére, Denise Belucio [UNESP]; Teixeira de Moraes Costa, Mariana Machado [UNESP]; Cunha, Robson Frederico [UNESP] (My University, 2009)
The purpose of this report was to describe the case of an 18-month-old boy who was referred to the pediatric clinic of the School of Dentistry of Araçatuba, São Paulo State University, Araçatuba, São Paulo, Brazil, 3 days after sustaining severe trauma that led to the complete intrusion of the primary maxillary right lateral incisor, a crown fracture of the primary maxillary right central incisor without pulp involvement, and disruption of the superior labial frenum. Four months later, spontaneous re-eruption was observed in the intruded tooth and no endodontic intervention was necessary in either traumatized teeth. Four years after the trauma, a morphological change in the germ of the permanent successor was noted. Clinical follow-up and periodic radiographies are necessary after traumatic intrusion of primary teeth to monitor possible sequelae in the permanent successors.
Keywords: Dental trauma; Intrusion; Primary; Tooth; case report; deciduous tooth; human; incisor; infant; injury; lip; male; radiography; tooth eruption; tooth fracture; Humans; Incisor; Infant; Labial Frenum; Male; Tooth Eruption; Tooth Fractures; Tooth, Deciduous